2018
DOI: 10.4274/tnd.76148
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Postural Balance Training Program on Balance, Gait and Health-Related Quality of Life in Patients with Essential Tremor

Abstract: Objective: Although the effectiveness of postural balance training on balance and gait impairment has been proven as an effective treatment approach in several patient and healthy populations, its effectiveness in patients with essential tremor (ET) is yet unknown. The aim was to examine the effects of postural balance training program on balance and gait performance, and health-related quality of life in patients with ET. Materials and Methods: This uncontrolled clinical study included patients with ET. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Two studies collected and reported information about multisensory exercise, which included participants all females [31,32] . Of these participants, 30 were ataxic patients [33] , 73 were older adults with a history of falls [20,34,35] , 33 were older adults without fall history [35,36] , 18 were older adults with visual impairment [37] , 16 were diabetics with peripheral neuropathy [38] , and 21 were patients with essential tremor [39] . A total of 667 participants were included in the 20 studies, four studies were conducted in the United States, four in Canada, two in Brazil, and two in France, other studies in England, Indian, Sweden, and so on.…”
Section: Participants and Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies collected and reported information about multisensory exercise, which included participants all females [31,32] . Of these participants, 30 were ataxic patients [33] , 73 were older adults with a history of falls [20,34,35] , 33 were older adults without fall history [35,36] , 18 were older adults with visual impairment [37] , 16 were diabetics with peripheral neuropathy [38] , and 21 were patients with essential tremor [39] . A total of 667 participants were included in the 20 studies, four studies were conducted in the United States, four in Canada, two in Brazil, and two in France, other studies in England, Indian, Sweden, and so on.…”
Section: Participants and Settingsmentioning
confidence: 99%
“…The total time spent in exercising during the multisensory exercise interventions varied from 0.5 [30,40] to 180 h [33] , while the intervention duration ranged from 2 [41] to 16 weeks [31] . Studies of intervention time showed that multisensory exercises worked within 6 weeks [34,38,42] , 8 weeks [20,39,43] , 12 weeks [36,37,44] ) respectively. However, there are still studies which reported effective intervention duration was less than 6 weeks or more than 12 weeks.…”
Section: Intervention Programsmentioning
confidence: 99%
See 1 more Smart Citation